2016
DOI: 10.1001/jamadermatol.2016.1776
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Hormonal Profile of Early Androgenetic Alopecia in Men With the Phenotypic Equivalent of Polycystic Ovarian Syndrome in Women

Abstract: IMPORTANCE Early androgenetic alopecia (AGA) is patterned hair loss occurring before age 30 years. Early AGA in men is frequently reported as the phenotypic equivalent of polycystic ovarian syndrome (PCOS) in women, which carries the risk of developing obesity, metabolic syndrome, and cardiovascular diseases. Very few studies have been conducted to evaluate this.OBJECTIVE To study the hormonal profile of men with early AGA and to evaluate if early AGA in men can be considered as the phenotypic equivalent of PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
49
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 21 publications
10
49
1
Order By: Relevance
“…AGA is characterized by miniaturization of hair follicles with the transformation of terminal hair follicles into vellus‐like ones. Increased levels of testosterone have been found among men with early AGA . Women do not have higher levels of circulating androgens, but they have higher levels of type I and II 5 alpha reductase, more androgen receptors, and lower levels of aromatase enzyme …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…AGA is characterized by miniaturization of hair follicles with the transformation of terminal hair follicles into vellus‐like ones. Increased levels of testosterone have been found among men with early AGA . Women do not have higher levels of circulating androgens, but they have higher levels of type I and II 5 alpha reductase, more androgen receptors, and lower levels of aromatase enzyme …”
Section: Introductionmentioning
confidence: 99%
“…Increased levels of testosterone have been found among men with early AGA. 7 Women do not have higher levels of circulating androgens, but they have higher levels of type I and II 5 alpha reductase, more androgen receptors, and lower levels of aromatase enzyme. 2 It has been suggested that AGA is an androgen-related condition in genetically predisposed individuals; 8 however, genetic predisposition cannot explain the whole risk associated with the condition neither with its severity.…”
Section: Introductionmentioning
confidence: 99%
“…If real, this could reflect that male pattern male pattern baldness, or androgenetic alopecia, is mediated by dihydrotestosterone, the potent metabolite of testosterone . There is growing evidence suggesting that male pattern balding status could serve as a clinical marker for circulating sex hormone concentrations . Moreover, preclinical experimental evidence supports a gastric cancer‐promoting effect for testosterone and androgen receptor overexpression in vivo has been shown to promote cell migration, invasion and proliferation in gastric cancer .…”
Section: Discussionmentioning
confidence: 99%
“…35 There is growing evidence suggesting that male pattern balding status could serve as a clinical marker for circulating sex hormone concentrations. [36][37][38] Moreover, preclinical experimental evidence supports a gastric cancerpromoting effect for testosterone 12 and androgen receptor overexpression in vivo has been shown to promote cell migration, invasion and proliferation in gastric cancer. 20 Taken together, it is possible that androgens might play a role in the development of these cancers, and could provide a logical explanation for the male dominance in their incidence.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 Direct comparison of results from epidemiological studies on circulating sex hormones in relation to male pattern baldness is challenging given differences in age, race, laboratory assays (eg, RIA, mass spectrometry, electrochemiluminescence immunoassay), health status (with/without malignancy/other metabolic diseases), and balding categories. Several small studies (n = 6) have assessed this relationship among apparently healthy younger (<45 years old) men and found conflicting associations; some reported that bald men were more likely to have increased testosterone, 15,42 increased testosterone/SHBG ratio, 42,43 increased DHT 15 and decreased SHBG levels, [42][43][44] whereas others have reported either null or opposing findings. 45,46 On the other hand, a cross-sectional study among older (>65 years) healthy Greek men specifically compared vertex balding to those without (ie, no/minimal plus frontal balding only) and did not find associations for serum testosterone, estradiol, DHEA-S, or SHBG.…”
Section: Discussionmentioning
confidence: 99%